Improving Light Distribution by Zoom Lens for Electricity Savings in a Plant Factory with Light-Emitting Diodes - Li, Kun; Li, Zhipeng; Yang, Qichang (Frontiers in Plant Science, 2016)
The high-energy consumption of plant factory is the biggest issue for its rapidly expanding, especially for the lighting electricity, which have been solved to a large extent by light-emitting diodes (LED). However, remarkable potentiality in energy saving remains to be further investigated. In this study, an optical system applied just below LED was designed. The effects of the system on growth and photosynthesis of butterhead lettuce (Lactuca sativa var. capitata) were examined, and the performances of the optical improvement on energy saving were evaluated by comparison with the traditional LED illumination mode. The irradiation patterns used were LED with zoom lenses (Z-LED) and conventional non-lenses LED (C-LED). Seedlings in both treatments were exposed to the same light environment during the entire growth period. The improvement saved over half of the light source electricity, while lower the temperature of Z-LED prominently. Influenced by this, the photosynthesis sharply decreased and further caused reduction in plant yield and nitrate content, while exhibited no negative effects on morphological parameters and photosynthetic pigment contents. Nevertheless, the much higher light use efficiency of Z-LED made this system a better approach of illumination in a plant factory with artificial lightings.